An interpretative phenomenological study of midwives supporting home birth for women with complex needs - Madeley, A-M; Williams, V; McNiven, A (Mark Allen Group, 2019)
Background As the landscape of women presenting for maternity care changes, so do the challenges associated with providing quality, informed and compassionate care, particularly for women with complex needs.